SISTEM INFORMASI PENGOLAHAN DATA JEMAAT GEREJA HKBP CIKARANG KOTA BERBASIS WEBSITE - Simanjuntak, Antonius; Maulana, Donny; Widodo, Edy (IDEALIS : InDonEsiA journaL Information System, 2024)
The web-based church congregation information system has become a modern solution that makes it easier for churches to manage congregation data and church activities more efficiently and organized. This research reviews the implementation of the church congregation information system in HKBP Cikarang City which previously used manual methods with notebooks. The main problem faced is the limitations of manually managing congregational data which often results in inaccurate data and operational inefficiencies. By implementing a web-based information system using the Waterfall method, this research aims to increase the efficiency and accuracy of congregation data management. The research results show that the information system developed is able to increase the accuracy of congregational data and reduce data management time by up to 60%, while increasing data accessibility for church administrators. These findings provide support that the implementation of a web-based information system can provide an effective solution to overcome the challenges of managing congregational data faced by HKBP Cikarang City. This system can be adapted and applied to other churches that have similar needs, thereby increasing the efficiency and accuracy of congregation data management in various churches.